Application of mindfulness-based interventions – MBCT and MBSR – in depression treatment and relapse prevention - Szymonik, Julia; Szopa, Sebastian (Quality in Sport, 2024)
Introduction: Depression stands as a primary contributor to disability, prompting extensive exploration of treatment and prevention strategies. Recognizing the limitations of conventional approaches, the significance of effective non-pharmacological therapies, like psychotherapy, in managing mental health disorders is increasingly acknowledged. There’s a growing interest in mindfulness-based interventions such as Mindfulness-Based Cognitive Therapy (MBCT) and Mindfulness-Based Stress Reduction (MBSR). These interventions, which prioritize present-moment awareness and acceptance, target depression’s mechanisms, such as rumination, while cultivating coping strategies and resilience. Mindfulness, with its comprehensive approach and capacity for self-regulation, emerges as pivotal in addressing psychiatric conditions. This paper aims to provide a comprehensive evaluation of MBCT and MBSR’s effectiveness in treating depression and preventing relapses. Description of the state of knowledge: MBCT and MBSR exhibit promising potential in effectively managing and preventing depression. Moreover, they alleviate anxiety, emotional exhaustion, stress and psychological distress, while fostering improved coping with rumination, memory disturbances and emotional regulation. Summary: Research indicates that incorporating MBCT and MBSR could offer a hopeful avenue for managing and alleviating the symptoms of depression and mental disorders, by addressing underlying factors which play a pivotal role in their development. To corroborate these encouraging results, additional randomized, large-scale, placebo-controlled trials are essential.